Model Penguatan Pendidikan Karakter pada Sekolah Perjumpaan di Nusa Tenggara Barat - Wahab Wahab; Ahmad Muntakhib (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
The character of students should be able to describe the implementation of the educational process. However, so far, the educational process has emphasized more knowledge orientation than character building. It is reflected in the pride of almost every educational institution if its students succeed in achieving a high National Exam or UAN Final Score. This orientation is supported by the growth and development of tutoring institutions, private lessons, study groups, or teacher rooms. This condition triggers a real thought and action to restore the primary function of education as character building. One model of strengthening character education is through the community of Sekolah Perjumpaan in West Nusa Tenggara. This research is qualitative research with a case study approach. The subjects of this study were student participants in the Sekolah Perjumpaan in West Nusa Tenggara. This research was conducted at the community point of Sekolah Perjumpaan in Bangket Bilong Village, Midang, Mantang, and at the initiator of the Sekolah Perjumpaan. This study found that the Sekolah Perjumpaan is a model of strengthening character education, positioning students as subject to subject, and awakening students to fulfill each participant's obligations as complementary beings collectively. Thus, the character education model of the Sekolah Perjumpaan can be applied in other educational institutions.